Tetrodotoxin prevents heat-shock induced granule cell dispersion in hippocampal slice cultures - Ahrari, Ala; Meseke, Maurice; Förster, Eckart (Frontiers in Cell and Developmental Biology, 2022)
Granule cell dispersion (GCD) has been associated as a pathological feature of temporal lobe epilepsy (TLE). Early-life epileptiform activity such as febrile seizures has been proposed to have a causal link to developing chronic TLE. During postnatal development, the hippocampus may be particularly vulnerable to hyperexcitability-induced insults since neuronal migration and differentiation are still ongoing in the hippocampus. Further, the extracellular matrix (ECM), here in particular the protein reelin, has been implicated in the pathophysiology of GCD. Thus, loss of reelin-expressing cells, Cajal-Retzius cells and subsets of interneurons, may be related to GCD. To study the possible role of febrile seizures, we previously induced GCD in vitro by subjecting hippocampal slice cultures to a transient heat-shock, which was not accompanied by loss of Cajal-Retzius cells. In order to examine the mechanisms involved in heat-shock induced GCD, the present study aimed to determine whether such dispersion could be prevented by blocking cellular electrical activity. Here we show that the extent of heat-shock induced GCD could be significantly reduced by treatment with the sodium channel blocker tetrodotoxin (TTX), suggesting that electrical activity is an important factor involved in heat-shock induced GCD.